Health Determinants of Asthma among Hispanic/Latino Children Enrolled in the Michigan Migrant and Seasonal Head Start Programs - Farabi, Nabila; Song, SuJin; Crockett, Elahé T.; Song, Won O. (Journal of Child Science, 2019)
Increasing prevalence of asthma in children in the United States is a major public health issue. Children in the Migrant and Seasonal Head Start (MSHS) program are one of the most vulnerable populations in the United States, with high rates of health disparities. We examined health determinants of asthma among Hispanic/Latino children enrolled in the Michigan MSHS programs. This study was a secondary data analysis based on the 2012 to 2013 ChildPlus dataset collected by Michigan Telamon Corporation. Sociodemographic and health information of 905 children aged 0 to 5 years was obtained from the dataset. Data were collected through interviews with parents by Telamon's specialists at each of the 18 Michigan MSHS centers. To determine children having asthma, health specialists at each center asked parents if their child/children had ever received asthma treatment. Weight status of children was categorized into nonoverweight/obese, overweight, and obese according to age- and sex-specific World Health Organization and Centers for Disease Control and Prevention growth chart standards. Multivariate logistic regression was used to identify asthma determinants. The overall prevalence of taking asthma treatment among Michigan MSHS children was 5.5%. Obese children had a higher odds ratio (OR) of asthma compared with nonoverweight/obese children (OR: 2.52; 95% confidence interval: 1.33–4.78). Children's age, health insurance status, and mothers' employment status were associated with asthma (p-values < 0.05). MSHS children are vulnerable to asthma, and their sociodemographic and obesity status are key determinants of having asthma. Identifying determinants of asthma might be helpful to design health policies and programs as well as implement health services for this population.
Keywords: asthma; childhood obesity; Hispanic/Latino children; Migrant and Seasonal Head Start